Inddragelse af informanter ved ordbogsarbejde - Bergenholtz, Henning; Jensen, Sanne (LexicoNordica, 2000)
In the introduction to many dictionaries very often a number of informants are gratefully mentioned. Normally, you are not informed about the number of informants or about the kind of questions which were given. In very few dictionaries, you will find information about those answers in the dictionary entries as well. In this paper, we will try to show how such informants could be included more systematically, especially by the description of grammatically and ortographically doubtful words.